KOMPOSISI JENIS HERBA PASCA KEBAKARAN DI KALAMPANGAN-KALIMANTAN TENGAH SEBAGAI AWAL PROSES SUKSESI SEKUNDER - Sadili, Asep (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
In the early stage of secondary succession process in 1 year old fost fire Kalampangan feat swamp area it was conducted a study on herbaceous plant species composition. The research found 6 fern species and 1 grass species out of 23 species representing 20 families. The coverage area of herbaceous vegetation was 13.12% or 1.312 m2 per hectare, which indicated relatively low percentage. In terms of relative dominance and frequency, herbaceous plant species in the area study was highly dominated by a terrestrial fern Stenochlaena palustris. Some tree species known as secondary and primary forest constituents such as Macaranga caladifolia (Euphorbiaceae), Dyera lowii (Apocynaceae), Combretocarpus rotundatus (Combretaceae), Cratoxylon arboresncens (Clusiaceae), Garcinia sp. (Clusiaceae) and Ploinarium alterifolium (Theacee) were found at their early growth stage on the forest floor but still in lower abundance compared to other recorded species from the study.